الإسلاموفوبيا باعتبارها خطاب كراهية: جذورها الدينية والثقافية: Islamophobia from a Hate Speech: Its Religious and Cultural Roots - Benlahcene, Badrane (Journal of Al-Tamaddun, 2022)
This paper raises a question about Islamophobia as a phenomenon in the Western context, and its resulting hate speech, to understand the roots of this phenomenon that produces hate speech towards Islam and Muslims. It aims to break down these historical roots, and relies on the analysis of religious texts from western religious personalities since the dawn of Islam until today, as well as the analysis of a some of intellectual texts expressing Western supremacy over Islamic civilization, which led to the emergence of Islamophobia and its transformation into hate speech in various means of communication and interaction. Among the results that this paper aspires to is to pave the way for religious and intellectual revision of western standpoint towards Islam, to open the door for new understanding of Islam and Muslims that goes beyond the complexities of the Crusades and the colonial period, to build an informed understanding of Islam and Muslims. Moreover, to open the door for cultural cooperation and coexistence instead of conflict, especially as we are in a world where the destiny of the whole humankind has become interconnected.